Progression of carotid near-occlusion to complete occlusion: related factors and clinical implications. (10th April 2020) - García-Pastor, Andrés; Gil-Núñez, Antonio; Ramírez-Moreno, José María; González-Nafría, Noelia; Tejada, Javier; Moniche, Francisco; Portilla-Cuenca, Juan Carlos; Martínez-Sánchez, Patricia; Fuentes, Blanca; Gamero-García, Miguel Ángel; Alonso de Leciñana, María; Masjuan, Jaime; et al.
Abstract : Background: The clinical consequences and factors related to the progression from a carotid near-occlusion (CNO) to a complete occlusion are not well established. Our aim is to describe the rate, predictive factors and clinical implications of the progression to complete carotid occlusion (PCCO) in a population of patients with symptomatic CNO. Methods: We conducted a multicenter, nationwide, prospective study from January 2010 to May 2016. Patients with angiography-confirmed CNO were included. We collected information on demographic data, clinical manifestations, radiological and hemodynamic findings, and treatment modalities. A 24 month carotid-imaging follow-up of the CNO was performed. Results: 141 patients were included in the study, and carotid-imaging follow-up was performed in 122 patients. PCCO occurred in 40 patients (32.8%), and was more frequent in medically-treated patients (34 out of 61; 55.7%) compared with patients treated with revascularization (6 out of 61; 9.8%) (p<0.001). 7 of the 40 patients with PCCO (17.5%) suffered ipsilateral symptoms. Factors independently related with PCCO in the multivariate analysis were: age ≥75 years (OR 2.93, 95% CI 1.05 to 8.13), revascularization (OR 0.07, 95% CI 0.02 to 0.20), and collateral circulation through the ipsilateral ophthalmic artery (OR 3.25, 95% CI 1.01 to 10.48). Conclusions: PCCO occurred within 24 months in more than half of the patients under medical treatment. Most episodes of PCCO were not associated with ipsilateral symptoms. Revascularization reduces the risk of PCCO.